Vitamin D Supplementation Improves Uterine Receptivity in a Rat Model of Vitamin D Deficiency: A Possible Role of HOXA-10/FKBP52 Axis - Hend Ashour (Frontiers Media S.A., 2021)
Synchronized uterine receptivity with the time of implantation is crucial for pregnancy continuity. Vitamin D (VD) deficiency has been linked to the failure of implantation. Therefore, we tested the link between the Homeobox transcription factor-10/immunophilin FK506-binding protein 52 (HOXA-10/FKBP52) axis and the uterine receptivity in VD-deficient rats. The effect of VD supplementation at different doses was also investigated. Forty-eight pregnant rats were divided into six groups (eight/group); normal control rats fed with standard chow (control), control rats supplemented with VD (equivalent dose of 400 IU/day) (control-D400). VD-deficient group (DEF) and the three VD deficiency groups with VD supplementation were equivalent to 400, 4,000, and 10,000 IU/day (DEF-D400, DEF-D4000, and DEF-D10000, respectively). The expression levels of HOXA-10/FKBP52, progesterone level, and histological evaluation of decidualization using osteopontin (OSN) and progesterone receptor (PGR) were estimated. An assessment of the uterine contractility was conducted for all rats. This study showed the downregulation of HOXA-10/FKBP52 together with increased amplitude and frequency of the uterine contractility in the DEF group compared to control. VD dose-dependent supplementation restored progesterone/receptor competency, upregulated the expressional response of HOXA-10 and its downstream FKBP52, and improved uterine receptivity and endometrial decidualization at the time of implantation that was documented by increased area% of OSN and the number of implantation beads.